Fluoride emission rate analysis in proton exchange membrane water electrolyzer cells - Kuhnert, Eveline; Heidinger, Mathias; Bernroitner, Anna; Kiziltan, Özge; Berger, Erwin; Hacker, Viktor; Bodner, Merit (Frontiers in Energy Research, 2024)
The assessment of PEM water electrolyzer (PEMWE) degradation is essential for understanding their long-term durability and performance under real-world conditions. This research focuses on the fluoride emission rate (FER) as a crucial parameter during PEMWE operation. Two different FER analysis methods are evaluated, considering their feasibility and ease of integration into a PEMWE system. An examination of different stressors during PEMWE operation is conducted to gain insights into membrane degradation and explore potential mitigation strategies. The utilization of a photometric detection method allowed for the quantification of FER in each test. The results highlight a noteworthy correlation between the applied stressors and the FER, with variations observed depending on specific test conditions. An accelerated stress test conducted for 100 hours revealed a high FER at the anode of 0.83 µg h -1 cm -2 during the initial testing phase. Correspondingly, energy dispersive X-ray (EDX) mapping vividly showed a reduction in Nafion™ content on the catalyst-coated membrane (CCM) surfaces, likely impacting proton conductivity and performance. Electrochemical results support these findings, indicating changes in performance metrics that correspond to the identified membrane degradation. protective coatings to reduce fluoride release and extend the lifetime of the electrolyzer. A scheme of a PEMWE cell with its primary components is presented in Figure 1. While Pt is coated at the cathode side of the PEM, Ir is required at the anode due to the harsh environment of the OER. Consequently, more stable diffusion media are also necessary at the anode compartment. These porous transport layer (PTL) materials consist of platinated Ti-fiber or sintered material [5]. At the cathode side, carbon-based gas diffusion layers (GDL) can be employed. The stateof-the-art materials used as PEM currently consist of PFSA-based polymers with a PTFE backbone and sulfonic acid end-groups that provide protonic conductivity. The membrane thickness is typically around 100 µm with a trend to thinner materials [6]. Thinner materials, while offering advantages like lower resistance, may exhibit increased gas crossover.